Inflation, Wage Behaviour and Labor Mobility - Porter, Allan (Relations industrielles / Industrial Relations, 1969)
The author considers briefly the cost-push doctrine and why, if one accepts it, guidelines appear to be the logical remedy for inflation. This analysis is followed by an examination of Canadian wage behaviour, ending with particular attention to the effectiveness of the Canadian wage system in allocating manpower throughout the economy.